Protein Composition of the Anthelmintic Plant, Lupinus albus Linn. (Seeds) - Kumar Kuanar, Saroj (Asian Journal of Chemistry, 2010)
In this work the author identified different amino acids in the seeds of Lupinus albus (N.O.Leguminosae).